RENEWABLE ENERGY SOURCES AS A STRATEGIC VECTOR OF DIVERSIFIED POST-WAR ENTERPRISE DEVELOPMENT - NAMIASENKO, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The Russian war against Ukraine, with natural, economic, and historical factors, has created specific and demanding conditions for post-war recovery and development. These conditions are marked by the unsatisfactory state and limited efficiency of the national economic system, despite the significant availability of natural resources.A main instrument for solving these challenges is the diversified development of Ukraine’s largest companies within the framework of the national development strategy. A central direction of such diversification is defined as the expansion of energy generation from renewable energy sources (RES). The identification of opportunities for post-war recovery through the development of RES was set as the primary objective of this research.The findings indicate that the RES sector constitutes the branch of the energy system most suitable for independent management by both legal entities and individuals. At the same time, specific segments of the energy sector have been identified that should remain under state control (fully or partially). The analysis highlights the significance of bioenergy as an initial stage of diversification for agroholdings, with further development of solar and wind energy. An expanded range of advantages of biogas plants is also presented, demonstrating their role not only in financial growth but also in improving environmental sustainability.Possible scenarios for the development of RES are also examined, with particular emphasis placed on the critical role of the state in this process. The advancement of RES will exert a positive impact not only on the stability and independence of the energy system but also on related and service-oriented sectors of the economy.The overall conclusion emphasises the unequivocal necessity of RES development and its stimulation by the state as a strategic element of national energy independence and economic efficiency, both at the level of individual enterprises and for the whole Ukrainian economy.
Keywords: RES; WPP; SPP; Bioenergy; Alternative Energy Sources; Business Diversification; Post-War Development